Establishment of hairy root lines and analysis of iridoids and secoiridoids in the medicinal plant Gentiana scabra - Huang, Shih-Hung (Bot Stud, 2014)
BACKGROUND: Gentiana scabra is commonly known as ‘Longdan’ is an important herb in traditional Chinese medicines, commonly used for the treatment of inflammation, anorexia, indigestion and gastric infections. Iridoids and secoiridoids are main bioactive compounds which attributed to the pharmacological properties of this plant. The use of hairy root cultures as an excellent alternative for the production of pharmaceutically important metabolites in less time period with ensured quality of raw materials. RESULTS: An efficient hairy root culture system of Gentiana scabra and influence of different plant growth regulators (PGRs) on the production of gentiopicroside, swertiamarin and loganic acid constituents were described. Leaf explants were infected with Agrobacterium rhizogenes, which induced hairy roots up to 21%. The transformed hairy root lines were confirmed by PCR using rolB and rolC gene-specific primers. Among various solid and liquid media, B5 liquid medium resulted maximum root biomass (36- fold higher) in 4-weeks. Quantitative analysis showed loganic acid was 6.6- fold higher in the presence of zeatin (1 mg/l) and gentiopicroside accumulation was 1.8- fold higher in the presence of naphthaleneacetic acid (NAA, 1 mg/l), as compared to the roots of plants grown in greenhouse. On the other hand, 1.4- and 2.5- fold higher gentiopicroside and swertiamarin were observed in the presence of 1.0 mg/l NAA as compared to commercial Gentiana herb No. 2. The result also showed iridoid and secoiridoid contents affected greatly by age, physiology and growing environment of the plant. CONCLUSIONS: The use of hairy root cultures is an excellent alternative to harvesting natural or in vitro grown plants to produce pharmaceutically important metabolites in less time with ensured quality. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1999-3110-55-17) contains supplementary material, which is available to authorized users.